Exploring the influence of practice design on the development of tennis players - Krause, L. M. (Victoria University, 2019)
This thesis examined the efficacy of contemporary tennis practice for maximizing skill learning and transfer to competition performance. Theory suggests that experimental and practice tasks should be designed to promote emergent behaviours that are functional and adaptable to changing situations that occur during competition. Current evaluations of practice design in multiple sports, however, suggest that coaches do the opposite, prioritising tasks that promote mechanical consistency over adaptability. Practice in many sports may therefore be sub-optimal. To address this concern, Representative Learning Design (RLD) has been proposed as a framework for assessing the extent to which a task is representative of a situation of interest (e.g., an athletes competition environment). The terminology within the RLD framework, however, requires simplification for application by coaches in applied settings. Moreover, despite suggestions of its importance, no empirical work has assessed the longitudinal benefits of practicing in tasks more representative of competition contexts.This thesis combined the experiential and theoretical knowledge of experts in skill acquisition and tennis with concepts from RLD to design the Representative Practice Assessment Tool (RPAT). Application of the RPAT confirmed that tennis coaches prioritised tasks low in representativeness. This is a concern given it was also found that athlete behaviours observed in matchplay are best simulated in tasks that more closely represent matchplay contexts. Most importantly, this thesis provides empirical evidence which suggests that increasing the representativeness of a task does not simply imply enhanced skill learning, rather changes to task representativeness promotes different learning outcomes/adaptations that remain specific to how practice was conducted. To summarise, this thesis extended current knowledge of designing practice tasks for enhanced skill learning and transfer. Practitioners and coaches are recommended to individualise the representativeness of tasks to the specific needs of their athlete in a manner which facilities the emergence of functional behaviours that are transferable to competition.